Primulina hochiensis var. rosulata (Gesneriaceae)―a new variety at an entrance of a limestone cave from Guangxi, China - Wen, Fang; Qin, Guo-Le; Wei, Yi-Gang; Liang, Gui-You; Gao, Bo (Phytotaxa, 2012)
Primulina hochiensis var. rosulata, a new endemic variety from Guangxi, China, is described and illustrated. It is similar to P. hochiensis sensu stricto, but differs in lacking stolons, the different indumentum of peduncle, corolla, filament and anthers, leaf blades elliptical to slightly ovate, calyx purple, corolla white or pink, filaments geniculate close to the base, staminodes 3, and stigmas translucent to white, obtrapeziform, 2-lobed.